Focus groups reveal how threat vigilance hinders social needs screening and referrals in the emergency department - Bybee, Sara G.; Tedford, Natalie J.; Grigorian, Ernest G.; Luther, Brenda; Guo, Jia-Wen; Wong, Bob; Diamond, Lisa; Wallace, Andrea S. (Frontiers in Communication, 2025)
IntroductionScreening for unmet social needs (such as food or housing insecurity) in healthcare settings has the potential to promote patient health by connecting them with needed resources, but many patients decline to complete screening instruments. The purpose of this paper was to identify the barriers and facilitators of patient participation in social needs screening.MethodsBetween December 2022 and March 2023, we conducted four virtual focus groups with community-dwelling adults regarding social needs screening questions. Our sample included 32 adults (10 English-speaking and 22 Spanish-speaking). Based on current theoretical models of human threat vigilance, we coded participant speech into two broad categories: social threat (such as vulnerability, exclusion, and aggression) and social safety (such as helpfulness, inclusivity, and predictability). NVivo software was used to conduct qualitative analysis between May and December 2023.ResultsParticipants discussed social threats seven times more often than they discussed social safety, and all of these social threats were expectations (rather than experiences). In contrast, communication surrounding social safety centered on previous positive experiences, rather than expectations.DiscussionThese results align with the notion that human brains maintain a default state of threat vigilance until cues of safety and inclusion are detected. Accordingly, the only way to increase screening rates is to “head off” patients’ automatic threat vigilance with clear and concrete communication of social safety, before they are even given a screening instrument. These findings can assist healthcare organizations in developing “safety first” communication practices and screening protocols that can enhance screening and rates of successful follow-up.